Ethical questions concerning newborn genetic screening. Issue 1 (2nd September 2020) - Esquerda, Montserrat; Palau, Francesc; Lorenzo, David; Cambra, Francisco Jose; Bofarull, Margarita; Cusi, Victoria; Interdisciplinar en Bioetica, Grup
Abstract: Newborn screening is a public health strategy used to identify certain diseases in the first days of life and, therefore, facilitate early treatment before the onset of symptoms. The decision of which diseases should be included in a screening goes beyond the medical perspective, including reasons for public health and health economics. There are a number of characteristics to include a disease in the screening, such as that the disorder must be a significant health problem, the natural history of the disease must be well known, a feasible and accurate test must be available, there must be a treatment that is most effective when applied before the onset of clinical symptoms and a health system must be in place that is capable of performing the procedure and subsequent monitoring. Currently, newborn screening programs are currently based on the use of biochemical markers that detect metabolites, hormones or proteins, but recently, the availability of new technology has allowed the possibility of a genetic screening. In addition to technical problems, the possibility of neonatal screening also presents a number of ethical problems. We identified and discussed six areas of particular concern: type of illness, overdiagnosis or overtreatment, information management and informed consent, data confidentiality and protection, justice and legal regulation. Abstract :